PEMBATALAN TIKET OLEH CALON PENUMPANG MASKAPAI PENERBANGAN DI INDONESIA - Budimah Budimah (Maleo Law Journal, 2018)
The level of public dependence on air transport has developed very rapidly. Starting from a group of people who go for a holiday, until the business people who often travel abroad. In addition, the number of airlines has created a competitive climate between one airline and other airlines which in the end gave birth to cheap tickets enthusiastically hunted by the public. Therefore, it is necessary to enforce the legal arrangement of ticket cancellation by the prospective passenger due to certain reasons set forth in Article 10 Regulation of the Minister of Transportation Number 185 of 2015 on Standard of Passenger Economy Class Service of Domestic Scheduled Domestic Air Transportation. However, in this provision has not explicitly stipulated the provisions on the causes of flight cancellations from passengers, it would be detrimental for the airline because passengers can cancel tickets arbitrarily and Legal implications for airlines that do not want to return the money of prospective passengers due to cancellation ticket may then be subject to legal sanctions in the form of administrative sanctions, administrative sanctions granted to airlines in the form of freezing of permits or even revocation of air operations licensesKeywords : Refund Ticket,  Passengers